Wide-range weight functions and stress intensity factors for arbitrarily shaped crack geometries using complex Taylor series expansion method - Jing, Z.; Wu, X.R. (Engineering fracture mechanics, 2015)
•Wide-range weight functions for four crack geometries determined by WCTSE method.•WCTSE implemented using ABAQUS and MATLAB software.•Accuracy of WCTSE improved by using better series expansion expressions.•Green’s function and severe load conditions used for accuracy assessment.•Reference load case independence of WCTSE is demonstrated. The recently developed complex Taylor series expansion method for computing weight functions (WCTSE) of arbitrary 2D crack geometry is further studied. Improvements on several aspects are made to raise solution accuracy. Wide-range weight functions are determined for four different crack geometries. Methods for accuracy assessment using the Green’s function or severe load conditions are proposed. The WCTSE numerical weight function and the conventional analytical weight function approaches are shown to be complementary. It is envisaged that combination of the two approaches will lead to more widespread applications of the weight function methods for fracture and crack growth analyses.